Absolutely continuous energy bands and extended electronic states in an aperiodic comb‐shaped nanostructure. Issue 7 (19th May 2014) - Pal, Biplab
<x xml:space="preserve">Abstract</x> The nature of electronic eigenstates and quantum transport in a comb‐shaped Fibonacci nanostructure model is investigated within a tight‐binding framework. Periodic linear chains are side‐attached to a Fibonacci chain, giving it the shape of an aperiodic comb. The effect of the side‐attachments on the usual Cantor set energy spectrum of a Fibonacci chain is analyzed using the Green's function technique. A special correlation between the coupling strength of the side‐attached chain with the Fibonacci chain and the inter‐atomic coupling of the Fibonacci chain results in a conversion of the fragmented Cantor set energy spectrum into multiple sets of continuous sub‐bands of extended eigenstates. The result is valid even for a disordered comb and turns out to be a rare exception of the conventional Anderson localization problem. The electronic transport thus can be made selectively ballistic within desired energy regimes. The number and the width of such continuous sub‐bands can be easily controlled by tuning the number of atomic sites in the side‐coupled periodic linear chains. This gives us a scope of proposing such aperiodic nanostructures as potential candidates for prospective energy selective nanoscale filtering devices.